Pengaruh Self-Esteem terhadap Cyberbullying Victimization pada Remaja di Jawa Barat - Salsabila; Sulisworo Kusdiyati (UNISBA Press, 2023)
Abstract. Bullying is a problem that occurs a lot. Now with the development of technology and the internet, bullying does not only occur physically but also virtually or called cyberbullying. Based on several short questions given to high school/vocational high school teenagers in West Java, cyberbullying is a problem that is often encountered in modern times. As many as 16 out of 20 teenagers claimed to have been victims of cyberbullying. One of the predictors of cyberbullying victimization is the level of self-esteem. Someone with low self-esteem will have a higher risk of becoming a victim. This study aims to see how the effect of self-esteem on cyberbullying victimization that occurs in high school/vocational high school teenagers in West Java. This study uses the Rosenberg's Self-Esteem Scale and the Cyberbullying Victimization Scale by Patchin and Hinduja. This research was conducted on 204 respondents using a causal method with a quantitative approach and analyzed using a simple linear regression test. The results show that self-esteem is negatively related to cyberbullying victimization. That is, the lower the level of self-esteem, the higher the chances of a person experiencing cyberbullying victimization with high intensity. Abstrak. Bullying merupakan permasalahan yang banyak terjadi. Kini dengan semakin berkembangnya teknologi dan internet membuat bullying tidak hanya terjadi secara fisik tetapi juga secara virtual atau disebut dengan cyberbullying. Berdasarkan beberapa pertanyaan singkat yang diberikan pada remaja SMA/ SMK di Jawa Barat, cyberbullying merupakan permasalahan yang banyak ditemui di zaman modern ini. Sebanyak 16 dari 20 remaja mengaku telah menjadi korban cyberbullying. Salah satu prediktor dari cyberbullying victimization adalah tingkat self-esteem. Seseorang dengan self-esteem yang rendah akan memiliki risiko lebih tinggi untuk menjadi korban. Penelitian ini bertujuan untuk melihat bagaimana pengaruh self-esteem terhadap cyberbullying victimization yang terjadi pada remaja SMA/ SMK di Jawa Barat. Penelitian ini menggunakan alat ukur Rosenberg's Self-Esteem Scale dan alat ukur Cyberbullying Victimization Scale oleh Patchin dan Hinduja. Penelitian ini dilakukan pada 204 responden menggunakan metode kausal dengan pendekatan kuantitatif dan dianalisis menggunakan uji regresi linier sederhana. Hasil menunjukkan self-esteem berhubungan negatif terhadap cyberbullying victimization. Artinya, semakin rendah tingkat self-esteem maka semakin tinggi peluang seseorang untuk mengalami cyberbullying victimization dengan intensitas tinggi.